2022
DOI: 10.1016/j.esmoop.2021.100336
|View full text |Cite
|
Sign up to set email alerts
|

Real-world application of tumor mutational burden-high (TMB-high) and microsatellite instability (MSI) confirms their utility as immunotherapy biomarkers

Abstract: Introduction Microsatellite instability (MSI) testing and tumor mutational burden (TMB) are genomic biomarkers used to identify patients who are likely to benefit from immune checkpoint inhibitors. Pembrolizumab was recently approved by the Food and Drug Administration for use in TMB-high (TMB-H) tumors, regardless of histology, based on KEYNOTE-158. The primary objective of this retrospective study was real-world applicability and use of immunotherapy in TMB/MSI-high patients to lend credence to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
82
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(109 citation statements)
references
References 32 publications
3
82
0
1
Order By: Relevance
“…Biomarker results are often the rate-limiting step in initiating systemic therapy, particularly in diseases such as NSCLC. Previous studies from our group have showed the turnaround time of send-out testing to be as long as 64 days, with in-sourced rapid single-gene testing delivered with a turnaround of 4 days, and that this reduction in turnaround time is associated with reductions in time to systemic therapy initiation [9,12]. This study demonstrates that comprehensive NGS can also be offered rapidly, within 3 business days.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Biomarker results are often the rate-limiting step in initiating systemic therapy, particularly in diseases such as NSCLC. Previous studies from our group have showed the turnaround time of send-out testing to be as long as 64 days, with in-sourced rapid single-gene testing delivered with a turnaround of 4 days, and that this reduction in turnaround time is associated with reductions in time to systemic therapy initiation [9,12]. This study demonstrates that comprehensive NGS can also be offered rapidly, within 3 business days.…”
Section: Discussionmentioning
confidence: 57%
“…This approach to testing is costly and creates a lengthy and convoluted pathway to gaining complete biomarker data, which in turn can lead to delays in treatment [7,8]. One recent study reported a median turnaround time of 73 days using this approach [9].…”
Section: Introductionmentioning
confidence: 99%
“…Next to PD-L1 expression, MSI and TMB are biomarkers that have shown clinical utility in predicting response to immunotherapy [4,5]. Upon the inactivation of mismatch repair genes, DNA replication errors accumulate and result in a high number of neoepitopes that stimulate the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, the process of immune cell infiltration is complex, and some oncogenic pathways of driving mutations [ 51 ] or virus infections may also influence the activation of the immune response [ 56 ]. Thus, experimental validation will be needed in future work [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%